CONCEPT INTERPRETATION FIELD AS A CONDUCTOR BETWEEN CONCEPT UNIVERSALITY AND ITS LINGVOCULTURAL SPECIFICITY - Popova , Natalia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of the mechanisms of universal concepts transformation into linguocultural mental units, a significant place among which belongs to the concept interpretive field which is defined as a series of cognitive characteristics interpreting the concept image and its notional content during its personal or collective consciousness practical comprehension. Changes within the prototype core and the conceptual field, arising due to the expansion of concept interpretation field during its historical development, have been analyzed in the research. Due to the semantic-cognitive and comparative analysis, changes within the interpretive field of the Spanish concepts CABALLERO, BANDERA and MACHO have been determined. It was clarified that the expansion of the interpretation field is accompanied by the modification of concept notional, associative and axiological components under the influence of social, historical, psychological and emotional peculiarities of the Spaniards. These modifications are reflected in the evaluative, conceptual, paremiological, utilitarian and regulatory zones of the concept interpretative field. It is established that the acquisition of the linguistic-cultural specificity by a universal concept occurs during its transition from the philosophical, religious or state-ideological type of consciousness to the everyday-life one, where the concept is rethought by the Spaniards in accordance with their world view and life realities. The boundaries of the concept interpretation field are expanded by its intellectual reflection under the influence of the people’s historical memory and revealed in literary works, music, painting and cinematography.________________References• Vezhbickaya,A. Ponimanie kultur cherez posredstvo klyuchevyh slov [= Understanding of Cultures through Key Words] (Moskva, 2001), 288 (In Russ.).• Vorkachyov,S. G. ««Kuda zh nam plyt?»: – lingvokulturnaya konceptologiya: sovremennoe sostoyanie, problemy, vektor razvitiya [= "Where are We Going to Swim?" – Linguocultural Conceptology: Current State, Problems, Development Vector].» Yazyk, kommunikaciya i socialnaya sreda [= Language, Communication and Social Environment] 8 (2010): 5−27 (In Russ.).• Zholamanova,E. I. «Teoriya semanticheskogo polya: tradicii i novacii [= Theory of Semantics Fields: Traditions and Innovations].» AUCA Academic Review, Section 2: The Humanities (2009): 149–154 (In Russ.).• Karasik,V. I. Yazykovoj krug: lichnost, koncepty, diskurs [= Personality’s Language Environmental: Concepts, Discourse] (Volgograd, 2002), 477 (In Russ.).• Karaulov,Yu. N. Obshaya i russkaya ideografiya [= General and Russian Ideography] (Moskva, 1976), 356 (In Russ.).• Popova, Z.D., Sternin, I. A. Kognitivnaya lingvistika [= Cognitive linguistics] (Moskva, 2007), 314 (In Russ.).• Maslova,V. A. Kognitivnaya lingvistika [Cognitive linguistics] (Minsk, 2008), 272 (In Russ.).• Popova,N. M. «Abstraguvannya ta model bazovogo rivnya u formuvanni ispanskoyi nacionalnoyi svidomosti [= Abstraction and the Basic Level Model for Spanish National Consciousness Formation.].» Problemi semantiki, pragmatiki ta kognitivnoyi lingvistiki [= Problems of Smantics, Pragmatics and Cognitive Linguistics] 25 (2014): 358–367 (In Ucr.).• Russkij associativnyj slovar: v 2 t. [= Russian Associative Dictionary: in 2 vol.], tom 1 (Moskva, 2002), 1776 (In Russ.).• Stepanov,Yu. S. Koncepty. Tonkaya plenka civilizacii [= Thin Covering of Civilization] (Moskva, 2007), 248 (In Russ.).• BartolHernandez, J. A. «Disponibilidad léxica y seleccion del vocabulario. De moneda nunca usada [= Lexical Availability and Vocabulary Selection. Never Used Currency].» Estudios filologicos dedicados a Jose Enguita Utrilla [= Philological Studies Dedicated to Jose Enguita Utrilla] (Zaragoza, 2010): 85–107 (In Spanish).• Diccionario Histórico de la Lengua Española [= Historical Dictionary of the Spanish Language] (Madrid, 1951), access http://web.frl.es/DH.html (In Spanish).• «Prensa de España.» El País [= The Country], access www.elpais.es (In Spanish).• Geeraerts, D. Diachronic prototype semantics. A contribution to Historical Lexicology (Oxford, 1997), 207.• Luque Durán,J. D. Aspectos universales y particulares del léxico de las lenguas del mundo [= Universal and Particular Aspects of World Languages Tesaurus] (Granada, 2001), 665 (In Spanish).• Sanchís,A. «¿Hablamos de machismo? [Are We Talking about Machismo?].» El país [= The Country], access https://elpais.com/elpais/2018/01/23/opinion/ 1516724179_ 082385.html (In Spanish).